Numerical study of multiphase mixing of micron sized aggregates in opposed jets fluidized bed - Farid, Muhammad Usman; Unger, Laura; dos Santos, Dyrney Araújo; Bück, Andreas (Chemical Engineering Research & Design, 2026)
Fine aggregates are considered as essential elements in the production of a wide range of food, pharmaceutical as well as other chemical products. In process industry, mixing of such particles is a crucial operation which controls the quality, texture and attributes of the final product. However, mixing becomes quite challenging while dealing with cohesive particles because of strong inter particulate forces, mostly van der Waals or capillary forces. A strong external force is required to overcome the cohesive forces and eventually, to agitate and mix such aggregates. With several advantages, mixing of such aggregates can be carried out in gas phase regime using fluidized bed systems. However, gas-solid environment yields to turbulence multiphase flow dynamics which needs to be investigated for optimum performance. In the current study, a two-way coupled Euler-Lagrange CFD model has been developed for the investigation of hydrodynamics and mixing of multiphase flows in an opposed jets fluidized bed. In total two phases were selected including air as a gas phase whereas TiO2 was considered as the solid phase. Particles were placed in the domain at known quantity and different streams of air jet were injected with the help of three nozzles mounted in the bottom and side walls of the apparatus. As a result, fluid dynamically different zones were formed such as stressing zone and mixing zone. Increasing air flow rate, the suspension and mixing of particles is improved. However, very high air injections results in formation of wall bounded layer of particles which negatively effects the mixing. High particle concentration was found near the wall in case of air flow rate injected at a flow rate of 0.003 kg/s. Further investigations are planned in order to further explore effect of dynamic classifier, particle size distribution and mass loading.
CRIS-Team Scopus Importer:2026-02-06
Keywords: CFD; Cohesive particles; Fluidized bed; Mixing; Multiphase flow